MicroRNA-145 Protects against Myocardial Ischemia Reperfusion Injury via CaMKII-Mediated Antiapoptotic and Anti-Inflammatory Pathways. (10th September 2019) - Liu, Zhebo; Tao, Bo; Fan, Suzhen; Pu, Yong; Xia, Hao; Xu, Lin
Abstract : MicroRNA-145 (miR-145) has been shown to play an important role in cardiovascular system disorders; however, the underlying mechanism is not completely understood. The purpose of this study was aimed at elucidating the cardioprotective effects of miR-145 against myocardial ischemia/reperfusion (I/R) injury. We established a rat myocardial I/R model with 45 min left anterior descending coronary artery (LAD) occlusion and 2 h reperfusion. The levels of myocardial enzymes, apoptotic, inflammatory, and oxidative indices were determined. The arrhythmia score was assessed by programmed electrical stimulation (PES). Quantitative real-time PCR and western blot were applied to evaluate the expression levels of miR-145 and related target proteins, respectively. I/R injury decreased the expression of miR-145; however, upregulated miR-145 markedly reduced the elevation of ST segment, decreased corrected QT (QTc) intervals, and attenuated I/R-induced electrophysiological instability. Furthermore, miR-145 suppressed myocardium apoptotic, inflammatory, and oxidative response as well as the phosphorylation of Ca 2+ /calmodulin-dependent protein kinase II (CaMKII), ryanodine receptor2 (RyR2 Ser2814), apoptosis signal-regulating kinase 1 (ASK1), c-Jun NH2-terminal kinases (JNK), and nuclear translocation of nuclear factor kappa-B (NF- κ B) p65. In summary, overexpression of miR-145 alleviates I/R-induced myocardial electrophysiological instability and apoptotic and inflammatory response via inhibition of the CaMKII-mediated ASK1 antiapoptotic pathway and NF- κ B p65 anti-inflammatory pathways.